Strategic Management of Post-Disaster Socioeconomic Recovery in the Industrial Revolution 4.0 Era - Rifai Rifai; Andy Feftra Wijaya (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Socioeconomic recovery constitutes a crucial and strategic component of post-disaster management, grounded in the principle of building back better and safer. In the era of the Industrial Revolution 4.0, rapid and dynamic changes driven by information technology often produce field conditions that do not fully align with existing technical guidelines. This study aims to formulate a proposed model for socioeconomic recovery that integrates digital technology without disrupting administrative procedures while substantively achieving recovery objectives. This study employs a qualitative case study approach focusing on post-disaster communities in the era of the Industrial Revolution 4.0, utilizing interviews with Disaster Management Agencies, followed by thematic analysis. The findings indicate that technology utilization, such as promoting fostered products through digital marketplaces, can strengthen enabling, empowering, and protecting stages of community development. Moreover, locally based approaches emphasizing local issues, authority, and accountability enhance program relevance and sustainability. The study concludes that effective reform requires strengthening networking and partnerships through public-private partnership schemes and fostering pentahelix collaboration among government, business, community, academia, and media actors.